Horizon: CNV interpretation through rapid automated ACMG-aligned pathogenicity analysis - Mariam Eldesouky; Suhana Shiyas; Amirul Islam; Md. Nahid Hasan; Md. Tanvir Hossain; Hosneara Akter; Md. Saiful; Bakhrom K. Berdiev; Wolfgang M. Kuebler; Proton Rahman; Marc Woodbury-Smith; Syed M. Hasan; et al. (Human Genetics, 2026)

Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

Characterization and resource potential of rare earth elements in coal mine tailings and coal fly ash: A sustainable waste-to-value perspective - Istiak Ahmed; Farhana Yesmin; Mohammad Tofayal Ahmed; Mohammad Moniruzzaman; Mohammad Forrukh Hossain Khan; Md. Saiful Islam (Hydrometallurgy, 2026)

Epidemiological status of bovine viral diarrhea virus in water buffalo (Bubalus bubalis): A global systematic review and meta-analysis - Eaftekhar Ahmed Rana; Md. Saiful Islam; Belayet Hossain; Mieghan Bruce; Subir Sarker; Jully Gogoi-Tiwari; Jasim M. Uddin (Research in Veterinary Science, 2026)

Characterizing decision optimization strategies for managing climate change impacts on aquatic ecosystems and public health in Asia - Md. Abdullah Al Mamun Hridoy; Chiara Bordin; Md. Saiful Islam; Matteo Bodini; Azeez Olalekan Baki; S. M. Sertaz Islam; Niraj Bohora; Md Masum Reza; Mohtasim Fowad Jamee; Dewan Hasan Al Mostakim; Riazul Islam; Andleeb Masood; et al. (Aquatic Sciences, 2026)

Studying the geochemical processes of environmental radionuclide alterations in a coastal area in terms of lanthanides: Probabilistic radiological risk assessment - Zitu Kundu; Rahat Khan; Dipraj Roy; Arafat Islam Pranto; Devlina Saha Aishe; Khalid A. Ibrahim; Md. Saiful Islam; Abubakr M. Idris; Kamrun Naher; Dhiman Kumer Roy (Marine Pollution Bulletin, 2026)

Assessing microplastic fate through textile wastewater treatment plants: Stage-specific retention and removal performance - Rahat Mostofa Prantor; Md Saiful Islam; Md. Nurul Absar; Nafisa Anjum Rimi; Md. Rezaul Karim; Harinarayan Das; Gangadhar Andaluri (Journal of Environmental Sciences, 2026)

Future changes in precipitation patterns and extremes in major coastal cities of Bangladesh using CMIP6 multi-model ensemble - Fariha Islam Mou; AKM Saiful Islam; Mushrufa Mushreen Winey; Md. Saiduzzaman; Nusaiba Nueri Nasir; Md Shadman Sakib; Mohammad Asad Hussain (Theoretical and Applied Climatology, 2026)

Does gender influence the environment in Bangladesh? The contribution of human capital to environmental promotion - Md. Saiful Islam; Umama Baida; Tahir Akhtar (Journal of Environmental Studies and Sciences, 2026)

Genomic and phenotypic insights into the probiotic and antimicrobial potential of Bacillus amyloliquefaciens BCSIR-AJ strain from garlic chutney - Mohammed Ayaz; Md Murshed Hasan Sarkar; Mohammad Monerul Islam; Muhammad Irfanul Islam; Farjana Akter Koly; Md. Rakibul Hasan; Md Saddam Hossain; Saiful Islam (Archives of Microbiology, 2026)

Morpho-phenological and biochemical responses of maize (Zea mays L.) to salinity stress - Siddhartha Kumar Roy; Progna Shil; Tusar Kanti Roy; Abdullah Al Kafi; Omar Kayess; Bikash Chandra Sarker; Md. Shafiqul Islam Sikdar; Md. Yasin Ali; Mohammed Ziauddin Kamal; Md. Saiful Islam; Zulhilmi Ismail (Journal of Crop Science and Biotechnology, 2026)

Assessment of natural radioactivity with radiological hazards and spatial distribution of radionuclides in soils, sediments from coastal and non-coastal regions of southeastern Bangladesh - Md. Abadat Hossain; AKM Saiful Islam Bhuian; Mohammad Belal Hossen (Environmental Monitoring and Assessment, 2026)

A Comprehensive Review of Chemoinformatics: From Molecular Representation to Data-Driven Design - Md. Saiful Islam; Propa Sarker; Md. Momin Islam; Sahab Uddin Shamim; Sadit Bihongo Malitha; Kazi Imtiaz Ahmed Nakib; Md. Zahangir Alam; A.M. Sarwaruddin Chowdhury (Next Research, 2026)

Valorization of dairy industry waste streams via anaerobic digestion - Md Saiful Islam; Vivek V. Ranade (Journal of Environmental Management, 2026)

Geo-environmental processes for elemental distributions in the sediments of coastal rivers streaming through the mangrove estuary: Ecological risks assessment - Rahat Khan; Sifat Aysha; Fairose Tasnim; Md. Noman Hossain; Sheikh Md. Anowar Hossain; Md. Saiful Islam; Jolly Sultana; Abubakr M. Idris; Khalid A. Ibrahim; Md. Harunor Rashid Khan; Md. Bodhroddoza Shohag; Kamrun Naher; et al. (Environmental Research, 2026)

Multi-Target Biological Prospects of Persicaria viscosa (Buch.-Ham. ex D. Don) Supported by GC–MS-Based Phytochemical Profiling - Md Alfaz Hossain; Md. Shamim; Md. Saiful Islam; S. M. Yasin Shourav; Md. Riaz Hosen; Fahmida Mariam Fariha; Safaet Alam; Md. Rasul Karim (Journal of Pharmaceutical Innovation, 2026)

Integrated In Vitro Assessment of Morphological, Biochemical, and Molecular Responses to Salinity Stress in Potato (Solanum tuberosum L.) - Anika Tasnim Khan Mim; Abdur Rahim; Md Shakil Rahman Shoagh; Baishakhi Roy; Mohammad Saiful Islam; Amit Kumar Dutta; M Badrul Islam; R Karim; M Nasiruddin; M Monzur Hossain (American Journal of Potato Research, 2026)

Spatiotemporal trends and urban-climate interactions of land surface temperature dynamics across Bangladesh - Md. Riyadul Haque; Arman; Muhammad Moniruzzaman; Sujit Kumar Roy; A.K.M. Saiful Islam (Anthropocene, 2026)

Smallholder participation in premium rice markets in Bangladesh: A structural equation model for understanding production and marketing decisions - Md. Tanvir Ahmed; Mohammad Saidur Rahman; Matty Demont; Islam Abu Hayat Md Saiful Islam; Md. Salauddin Palash; Ishika Gupta; Prakashan Chellattan Veettil (Agricultural Systems, 2026)

Mechanistic Insights into PFAS Adsorption on Microplastics: Effects of Contaminant Properties and Water Chemistry - Md. Saiful Islam; Gangadhar Andaluri (Environmental Research, 2026)

Assessment of groundwater quality and human health risks using deterministic and probabilistic approaches in Chandina Upazila, Cumilla, Bangladesh - Md. Tahsinur Rahman; Mohammad Ismail; Sajib Ahmed; Sayed Abu Johany; Ajoy Deb Nath; Kanai Lal Das; Md Mozammel Haque; Mohammad Saiful Islam Bhuiyan (Environmental Geochemistry and Health, 2026)

Heavy metals in basic vegetables of the Bagerhat district, Bangladesh - Tusar Kanti Roy; Sudipta Kumar Nag; Md. Saiful Islam; Zulhilmi Ismail; Abubakr M. Idris (Food Additives & Contaminants Part B-Surveillance, 2026)

Radionuclides and heavy metal contamination in edible fish and shellfish from two Bay of Bengal estuaries: source apportionment and health risk assessment - Asaduzzaman; Saiful Islam; Samin Yeasar Risal; Shirin Akter; Yeasmin Nahar Jolly; Md Fahmidul Haque; Md Joynal Abedin; Pradip K. Bakshi (Marine Pollution Bulletin, 2026)

Seroprevalence, molecular characterization, biotyping, and associated risk factors of bovine viral diarrhea in dairy cattle in Bangladesh - Eaftekhar Ahmed Rana; Md Saiful Islam; Belayet Hossain; Abdul Ahad; David J. Hampson; Sam Abraham; Subir Sarker; Jully Gogoi-Tiwari; Jasim M. Uddin (Research in Veterinary Science, 2026)

Microplastic migration and ecological risk in municipal solid waste landfills: A comparative assessment of controlled and open dumping systems - Md. Nurul Absar; Md. Rezaul Karim; Rahat Mostofa Prantor; Md. Saiful Islam; Harinarayan Das; Gangadhar Andaluri; Ragib Hasan; Md Atif Arham; Ali Intisar (Journal of Environmental Chemical Engineering, 2026)

Productivity and weed control efficiency under zero-tillage wheat (Triticum aestivum L.) influenced by post-emergence herbicides in a high-pressure weed ecology of Bangladesh - Mst. Tanjina Islam; Akbar Hossain; Md. Sohidul Islam; Md. Shafiqul Islam Sikdar; Annika Jahan Aonti; Md. Parvez Kabir; Saiful Islam; Apurbo K. Chaki; Abdulrahman Alasmari; Ahmed Gaber; Alison M. Laing; Mahesh K. Gathala (Phytoparasitica, 2026)

Rooftop and surface garden soils in Bangladesh harbor diverse resistome profiles - M. Nazmul Hoque; Md. Liton Rana; Md Abu Ahsan Gilman; Pritom Kumar Pramanik; Md. Saiful Islam; Sadia Afrin Punom; Rabith Rahman; Jayedul Hassan; M. Shaminur Rahman; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; et al. (Environmental Monitoring and Assessment, 2026)

Bioactive components of Azadirachta indica (neem) leaf extract enhance immunity, health, and production parameters in broilers - Md. Shafiqul Islam; Md. Abu Rayhan Parvez; Saiful Islam; Md. Tanvir Hasan; Md. Ashraful Alam; Md. Najibul Hoque (Research in Veterinary Science, 2026)

Assessment of heavy metal contamination and associated risks in fish feed and pond-cultured fish - Tafsir Hasan; Md Tasif Amir Sufal; Sha Md Shahan Shahriar; Md Sarwar Hossain; Md Shohanur Rahman; Md Mahfujul Hasan; Sumaiya Dipti; Md Saiful Islam; Md Khairul Islam; Sayed M.A. Salam (Food Control, 2026)

Geochemical insights into the depositional environment dynamics of Gondwana sediments in the Tajpur Basin, Bangladesh - Md Mahmudul Hasan Rakib; Rahat Khan; Arabe Khan; Mehedi Hasan Ovi; Pradip Kumar Biswas; Md Saiful Islam; Md Ali Akbar; Javed Mallick; Hoang Thi Hang; Dhiman Kumer Roy (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Influence modeling analysis of blockchain incorporation in emerging economies for achieving sustainable development goals and net-zero carbon emissions: Implication of sustainable healthcare supply chains in Bangladesh - Mohammad Abu Shahriar Hossain; Anup Karmakar; Md Kamruzzaman; Md. Saiful Islam (Journal of Cleaner Production, 2026)

Driving impacts through science-practitioner partnership: Professionalising water service delivery in rural Bangladesh - Sonia Ferdous Hoque; Rob Hope; Katrina J. Charles; Mohammad Monirul Alam; Md Nurul Osman; Mohammad Saiful Islam Mazomder (Environmental Science & Policy, 2026)

Distribution, Sources and Risks of Environmental Radioactivity in Differential Environmental Components: Experimental Findings with Potential Environmental Management Approaches - Rahat Khan; Farzana Yasmin Nupur; Muhibul Munim; Md. Saiful Islam; Kazi Md. Masum; Abubakr M. Idris; Md. Harunor Rashid Khan; Saad Aldawood; Md. Ahosan Habib; Shafi M. Tareq (Water, Air, & Soil Pollution, 2026)

Automatic weed detection in paddy field: a review - Md. Monirul Islam; Siti Khairunniza-Bejo; Muhammad Saiful Ahmad Hamdani; Nur Azuan Husin (Journal of Plant Diseases and Protection, 2026)

Tracing source footprints of heavy metal(oid)s in coastal soils using traditional statistical techniques and machine learning data-driven models - Abu Reza Md Towfiqul Islam; Memet Varol; Javed Mallick; Md. Abdullah-Al Mamun; Md. Yousuf Mia; Md. Abu Bakar Siddique; Md Saiful Islam; Mst. Nazneen Aktar (Marine Pollution Bulletin, 2026)

Microplastic pollution in aquaculture species: Quantification and characterization in Tilapia and Pangas - Md. Rased Khan Manon; Md. Sazedul Hoque; Md. Ariful Alam; Md. Saiful Islam; Md. Arifur Rahman (Aquaculture, 2026)

Hybrid data-driven framework for interpretable prediction of nitrate and sulfate risks in coastal aquifers - Md. Abdullah-Al Mamun; Mst. Nazneen Aktar; Md Nashir Uddin; Mohaiminul Haider Chowdhury; Md. Saiful Islam; M. Safiur Rahman; Md. Ripaj Uddin; Md. Jakir Hossain; Anwar Zahid; Venkatramanan Senapathi; Abu Reza Md. Towfiqul Islam (Science of The Total Environment, 2026)

A phenology-guided approach for detecting grassland invasive species using satellite image time series - Md Saiful Islam; Hamed Gholizadeh; M. Ny Aina Rakotoarivony; Robert G. Hamilton; Samuel Fuhlendorf; Yuting Zhou; Smriti Shrestha (Remote Sensing Applications: Society and Environment, 2026)

Assessing heavy metals toxicity in marine bed sediments of the Bay of Bengal: A novel baseline study on geochemical speciation, source, and risks - Md. Saiful Islam; Nor Aida Mahiddin; Debolina Halder Hemy; Abdullah Al Bakky; Uttam Biswas Antu; Zulhilmi Ismail; Nusrath Jahan Dristy; Tusar Kanti Roy; Mahmudul Hasan; Khalid A. Ibrahim; Abubakr M. Idris (Marine Pollution Bulletin, 2025)

Knowledge, attitude and practices of primary livestock raisers regarding anthrax and anthrax vaccination of livestock in outbreak and non-outbreak areas of Bangladesh - Ireen Sultana Shanta; Kamal Hossain; Syed Sayeem Uddin Ahmed; Melissa Kadzik; Antonio R. Vieira; Taifur Rahman; Rita M. Traxler; Md Saiful Islam; Farhana Haque; Muhammad Belal Hossain; Sk Shaheenur Islam; Nurnabi Ahmed; et al. (Preventive Veterinary Medicine, 2025)

An ethnobotanical assessment of traditional medicinal plants for diabetes treatment in Rangamati Hill Tracts and Panchagarh District, Bangladesh - Md Harunur Rashid; Anika Tasnim; Md. Farhad Sarker; Saiful Islam (Next Research, 2025)

Performance of concrete incorporated with Calamus tenuis cane fiber under chloride and wet-dry cycles conditions - Most. Shuborna Khatun; Md. Shah Jamal; Md. Saiful Islam (Innovative Infrastructure Solutions, 2025)

Microplastic toxicity in fish: A potential review on sources, impacts, and solution - Md. Towhidul Islam; Uttam Biswas Antu; Md. Shifat Hossain; Joyti Rani Paul; Tahsin Hasan; Pronayan Singha; Sandip Mitra; Sk Md Shoib Hasan; Zulhilmi Ismail; Md. Saiful Islam; Taher Sahlabjii; Abubakr M. Idris (Aquatic Toxicology, 2025)

Integrated multi-trophic aquaculture (IMTA): enhancing growth, production, immunological responses, and environmental management in aquaculture - Alokesh Kumar Ghosh; Abul Farah Md. Hasanuzzaman; Shikder Saiful Islam; Md. Golam Sarower; Saroj Kumar Mistry; Shaikh Tareq Arafat; Khandaker Anisul Huq (Aquaculture International, 2025)

Documentation of major pests and spectrum of pesticide usage for tea agroecosystems in Bangladesh - Md. Abdul Maleque; A. F. M. Saiful Islam; Md. Moudud Ahmod; Md. Simon Islam; Rashidul Hasan; Kazi Noor-E-Alam Jewel; Md. Saifullah; H. Roaki Ishii (Agroforestry Systems, 2025)

Innovation and CO2 Emissions Nexus in the Top Ten Innovative Countries: The Role of Economic Growth and Disaggregated Energy Consumption - Md. Saiful Islam; Sk Habibur Rahaman (Emission Control Science and Technology, 2025)

Assessing Heavy Metals using ICP-MS in Fruits from the Developing World and their Associated Health Risks - Tusar Kanti Roy; Sk Arafat Hossain; Md. Saiful Islam; Md. Fuad Hasan; Mahjabin Mazrin; Bikash Chandra Sarker; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Biological Trace Element Research, 2025)

Detection of avian pathogenic Escherichia coli (APEC) and antimicrobial resistance in layer parent stock in Bangladesh: Insights into phenotypic and genotypic profiles - Md. Nowshad Atiq; Md. Saiful Islam; Md. Ashek Ullah; Nirab Chakroborty; Raihana Islam; Md. Liton Rana; Farhana Binte Ferdous; Md. Abdus Sobur; Mohammad Ferdousur Rahman Khan; Md. Tanvir Rahman (Research in Veterinary Science, 2025)

A review on sustainable valorization of pulp and paper sludge for energy and material applications - Md. Rakib Hasan; Saiful Islam; Md. Mostafizur Rahman; Hasan Jameel; Khandoker Samaher Salem (Next Research, 2025)

Exogenous Application of ZnO Nanoparticles (NPs) To Palliate Salinity Induced Oxidative Stress in Lettuce (Lactuca Sativa L.) Plant - Tusar Kanti Roy; Md. Saiful Islam; Uttam Biswas Antu; Mousumi Jahan Sumi; Israt Jahan Irin; Sk Arafat Hossain; Keya Akter; Mahjabin Mazrin; Nor Aida Mahiddin; Habiba Zannat Meem; Abdullah Al Bakky; Zulhilmi Ismail; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Weather shocks and child nutritional status in rural Bangladesh: Does labor allocation have a role to play? - Kirara Homma; Abu Hayat Md. Saiful Islam; Masanori Matsuura; Bethelhem Legesse Debela (Food Policy, 2025)

Future changes in hydro-climatic extremes of a large transboundary river basin using multi-model bias-corrected CMIP6 projections - Kh M Anik Rahaman; Md Saiduzzaman; AKM Saiful Islam; Zarin Tasnim; Indronil Sarkar; Md Shadman Sakib; Mohammad Asad Hussain (Environmental Science and Pollution Research, 2025)

Microplastic contamination in Rupsha River of Bangladesh and its impacts on fish species - Ahmed Shakik; Puja Brohomo; Md. Shahariar Kabir; Md. Saiful Islam; Mahmudul Hasan Mizan (Regional Studies in Marine Science, 2025)

Monitoring and Health Risks Assessment of Primordial Radionuclides in Vegetables and Agricultural Soils in Some Hilly Regions of Southeastern Bangladesh - Kazi Anisur Rahman; Rahat Khan; Md. Bazlar Rashid; Saad Aldawood; Md. Saiful Islam; Md. Tazul Islam; Md. Mohi Uddin; Abubakr M. Idris; Md. Harunor Rashid Khan; Md. Ahosan Habib; Dhiman Kumer Roy (Archives of Environmental Contamination and Toxicology, 2025)

Microplastic pollution in livestock farming in Bangladesh: a critical review of its key findings and mitigation strategies to address public health - Md Rashedunnabi Akanda; Md. Abu Kawsar; Md Shiblee Sadik Sabuj; Md. Ashik-Uz-Zaman; Md. Saiful Islam Siddiqui; Md. Anwar Hossain (Environmental Monitoring and Assessment, 2025)

A baseline toxicity assessment of sediment geochemistry, potentially toxic elements contamination, and ecological risk in sediment profiles of the Bay of Bengal coast, Bangladesh - Md. Saiful Islam; Abdullah Al Bakky; Nor Aida Mahiddin; Md. Towhidul Islam; Uttam Biswas Antu; Zulhilmi Ismail; Tusar Kanti Roy; Mahmudul Hasan; Kazi Aminul Islam; Avijit Sarkar; Khalid A. Ibrahim; Abubakr M. Idris (Regional Studies in Marine Science, 2025)

Preliminary Assessment of Essential and Potentially Toxic Elements in the Most Common Spices in a Developing Country: Health Hazard Implication - Md. Saiful Islam; Uttam Biswas Antu; Ruma Akter; Md. Shifat Hossain; Sujat Ahmed; Tusar Kanti Roy; Zulhilmi Ismail; Abubakr M. Idris (Biological Trace Element Research, 2025)

Micro-propagation and mass production of Lophopetalum Wightianum Arn., a globally threatened evergreen tree species in Bangladesh - Jahirul Islam; Waheeda Parvin; Kazi Khayrul Bashar; Saiful Alam Md. Tareq; Md. Jakir Hossain; Md. Mahbubur Rahman (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Compound Climate Extremes Under the Future Climate Change Scenarios: A Case Study of Chattogram City, Bangladesh - Lia Pervin; Md. Sabbir Mostafa Khan; Md. Saiful Islam; Nasreen Jahan (International Journal of Climatology, 2025)
Waterlogging during the monsoon and water shortness during the pre‐monsoon are increasingly affecting the socio‐economic condition of Chattogram City. It is suspected that, climate change will lead frequent occurrence of compound climate extremes in future, which may result in greater destructions compared to those caused by individual extremes alone. Hence, it is of particular interest to predict the future climate more precisely. In this study our effort was to improve the understanding the effects of climate change on future compound climate extremes, the trends, variabilities and seasonal patterns. Here, we have evaluated CMIP5 and CMIP6 models from the high resolution bias corrected CORDEX data, and the best performing data sets (CanESM2, CSIRO and GFDL) were selected for the future climate change analysis. Using both RCP 4.5 and RCP 8.5 scenarios for 2021–2060, and 2061–2099 period, significant upward trends were projected for the daily maximum and minimum temperatures. However, rainfall pattern showed more complex criteria for the future. The current study revealed that the warm and cold spell, as well as the wet and dry spell characteristics will be altered in the future. The joint analysis of future temperature and rainfall anomalies using copulas revealed two folds effects of climate change on the local hydrology. Projected decrease of rainfall while increase of temperature during the pre‐monsoon season will potentially cause water scarcity. On the other hand, increase of extreme rainfall during the monsoon will complicate the waterlogging problems in Chattogram region. In this study, we have identified the time and the extent of combined temperature and rainfall anomalies, that can amplify the adverse impact on the hydro‐climatology of Chattogram City. The insights gained from this study are crucial for effectively addressing and managing the complex future hydroclimatic challenges in this region.

Occurrence of trace elements in water, fish and shellfish from estuarine and coastal areas of the east coast of Bangladesh, northeast Bay of Bengal: Human health risk implications - Seema Rani; Md. Kawser Ahmed; Chen Keliang; Kazi Belayet Hossain; Abu Hena Md. Yusuf; K.M. Azam Chowdhury; Md. Habibullah-Al-Mamun; Makidul Islam Khan; Nor Aida Mahiddin; Zulhilmi Ismail; Md. Saiful Islam (Marine Pollution Bulletin, 2025)

Groundwater quality drivers in the drought-prone Thakurgaon District, Northwestern Bangladesh: An integrated fuzzy logic and statistical modeling approach - Abu Reza Md Towfiqul Islam; A.J. Raihan; Md. Yousuf Mia; Md. Saiful Islam; Subodh Chandra Pal; Tanmoy Biswas; Bilkis A. Begum; Tasrina R. Choudhury; Mohammed Ali Alshehri; Venkatramanan Senapathi; M. Safiur Rahman (Journal of Contaminant Hydrology, 2025)

Large-scale protein extraction from oat hulls using two hydrodynamic cavitation techniques: A comparison of extraction efficiency and protein nutritional properties - Jiafei Tang; Gulden Goksen; Md Saiful Islam; Vivek Ranade; Shay Hannon; Da-Wen Sun; Brijesh K. Tiwari (Food Chemistry, 2025)

Exploring the occurrence of Pseudomonas aeruginosa and comprehensive whole genome analysis of the bcsir_p4_s20 strain from municipal wastewater in Chattogram - Md. Nuruddin Mahmud; Momthahena Momoshed; Md. Faisal Ahamed Talukder; Jannatul Ferdous; Farjana Akter Koly; Saiful Islam (World Journal of Microbiology and Biotechnology, 2025)

An assessment of the spatial and temporal distribution of nitrate and trace element concentrations in groundwater in coastal districts of Bangladesh - Fairose Tasnim; Mahmudul Hasan; Md. Nazmus Sakib; Anwar Zahid; Mahfujur Rahman; Md. Saiful Islam; Md. Golam Muktadir (Science of The Total Environment, 2025)

Retraction notice to “Personal protective equipment-derived pollution during Covid-19 era: A critical review of ecotoxicology impacts, intervention strategies, and future challenges” [Sci. Total Environ. 887(2023) 164164] - Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md Saiful Islam; Subodh Chandra Pal; Aznarul Islam; Tasrina Rabia Choudhury; Md Refat Jahan Rakib; et al. (Science of The Total Environment, 2025)

Hydrochemical facies distribution, controlling mechanisms and natural background concentrations of major pollutants in Ganga-Yamuna interfluve aquifer, India - Izrar Ahmad; Saif Ahmad Khan; Mohd Shoeb; Saiful Islam; Md Afzal Khan (Environmental Pollution, 2025)

Microplastic characterization and factors influencing its abundance in coastal wetlands: insights from the world’s largest mangrove ecosystem, Sundarbans - Abu Sayeed Shafiuddin Ahmed; Md Masum Billah; Mir Mohammad Ali; Laodong Guo; Shahrina Akhtar; Md Khurshid Alam Bhuiyan; Md Saiful Islam (Environmental Science and Pollution Research, 2025)

A Comprehensive Assessment of Health Risks Associated with Heavy Metal Through Ingestion of Two Predominant Fish Species in a Developing Country - Tusar Kanti Roy; Sudipta Kumar Nag; Uttam Biswas Antu; Sk Arafat Hossain; Abdullah Al Bakky; Md. Tanvir Anjum; Bikash Chandra Sarker; Md. Rahamat Ullah; Fariha Farzana; Nor Aida Mahiddin; Ashish Biswas; Pronayan Singha; et al. (Biological Trace Element Research, 2025)

Optimizing coastal groundwater quality predictions: A novel data mining framework with cross-validation, bootstrapping, and entropy analysis - Abu Reza Md Towfiqul Islam; Md. Abdullah-Al Mamun; Mehedi Hasan; Mst. Nazneen Aktar; Md Nashir Uddin; Md. Abu Bakar Siddique; Mohaiminul Haider Chowdhury; Md. Saiful Islam; A.B.M. Mainul Bari; Abubakr M. Idris; Venkatramanan Senapathi (Journal of Contaminant Hydrology, 2025)

Remote Sensing and GIS-Based Landslide Susceptibility Mapping in a Hilly District of Bangladesh: A Comparison of Different Geospatial Models - Saiful Islam Apu; Noshin Sharmili; Md. Yousuf Gazi; Md. Bodruddoza Mia; Shamima Ferdousi Sifa (Journal of the Indian Society of Remote Sensing, 2025)

Application of Nanoparticles (NPs) to Ameliorate Abiotic Stress in Economically Important Crop Species: a Potential Review - Tusar Kanti Roy; Md. Saiful Islam; Nor Aida Mahiddin; Sk Arafat Hossain; Tatia Biswas; Uttam Biswas Antu; Sharmin Akter Serity; Jannatul Ferdawsi Miti; Sonia Akter; Smaranika Roy; Ashish Biswas; Mahjabin Mazrin; et al. (Journal of Crop Health, 2025)

Impact of synbiotic on growth performance, histo-architectural modulation of lymphoid organ, hematology, blood biochemistry and humoral immune response in naked neck chicken - Hemayet Hossain; Harimurti Nuradji; Mohammad Yousuf Miah; Muhammad Nazrul Islam; Md. Saiful Islam Siddiqui (Tropical Animal Health and Production, 2025)

A machine learning-based approach for flash flood susceptibility mapping considering rainfall extremes in the northeast region of Bangladesh - Md Enayet Chowdhury; A.K.M. Saiful Islam; Rashed Uz Zzaman; Sharfaraj Khadem (Advances in Space Research, 2025)

Retraction notice to “Managing the invisible threat of microplastics in marine ecosystems: Lessons from coast of the Bay of Bengal” [Sci. Total Environ. 889 (2023) 164224] - Al-Nure Mubin; Shahoriar Arefin; Md. Sonir Mia; Abu Reza Md. Towfiqul Islam; A.B.M. Mainul Bari; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; M. Safiur Rahman; Venkatramanan Senapathi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2024)

Emerging technologies for efficient water use in agriculture: A review of current trends and future directions - Uttam Biswas Antu; Md. Saiful Islam; Sujat Ahmed; Md. Arifuzzaman; Sawmitra Saha; Puja Rani Mitu; Aditya Raj Sarkar; Nor Aida Mahiddin; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Journal of Water Process Engineering, 2024)

Investigating soil physicochemical factors influencing trace element contamination at the semi-urban-rural home gardening interfaces on the Fiji Islands - Vimlesh Chand; Abu Reza Md Towfiqul Islam; Md Yousuf Mia; Md Saiful Islam; Md Abdullah Al Masud; Rahat Khan; Subodh Chandra Pal; Sudhir Kumar Singh; Rozleen Roslyn Deo (Geoderma Regional, 2024)

Impact of anthropogenic activities and the associated heavy metal pollution in Sundarbans waterways: threats to commercial fish and human health - Mir Mohammad Ali; Amit Hasan Anik; Md. Saiful Islam; Abu Reza Md. Towfiqul Islam; Shantanu Kumar Saha; Md. Abu Bakar Siddique (Environmental Monitoring and Assessment, 2024)

A comprehensive analysis of health risks from metal contamination in the Sundarbans mangrove forest ecosystem in Bangladesh - Md. Mer Mosharraf Hossain; Shoumik Mojumdar; Md. Saiful Islam; Md. Anisur Rahman; Tahani Awad Alahmadi; Mohammad Javed Ansari; Saroj Kumar Mistry (Toxicology and Environmental Health Sciences, 2024)

Occurrence, characteristics and distribution of microplastics in commercial marine fishes of the Bay of Bengal - Pronoy Mondal; Md. Sazedul Hoque; Md. Arifur Rahman; Md. Mahmudul Hasan; Suprakash Chakma; Muhammad Saiful Islam; Md. Shahjahan (Marine Pollution Bulletin, 2024)

Predicting groundwater phosphate levels in coastal multi-aquifers: A geostatistical and data-driven approach - Md. Abdullah-Al Mamun; Abu Reza Md Towfiqul Islam; Mst. Nazneen Aktar; Md Nashir Uddin; Md. Saiful Islam; Subodh Chandra Pal; Aznarul Islam; A.B.M. Mainul Bari; Abubakr M. Idris; Venkatramanan Senapathi (Science of The Total Environment, 2024)

Toxicity assessment of heavy metals translocation in maize grown in the Ganges delta floodplain soils around the Payra power plant in Bangladesh - Md Saiful Islam; Abdullah Al Bakky; Sujat Ahmed; Md Towhidul Islam; Uttam Biswas Antu; Md Sadik Mahmud Saikat; Ruma Akter; Tusar Kanti Roy; Yeasmin Nahar Jolly; Kazi Aminul Islam; Avijit Sarkar; Zulhilmi Ismail; et al. (Food and Chemical Toxicology, 2024)

Toxicity factors, ecological and health risk assessments of heavy metal in the urban soil: a case study of an agro-machinery area in a developing country - Md. Saiful Islam; Abdullah Al Bakky; Md. Sadik Mahmud Saikat; Uttam Biswas Antu; Ruma Akter; Tusar Kanti Roy; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Environmental Geochemistry and Health, 2024)

Trace element contamination in water and sediment in an estuarine ecosystem connected to the Bay of Bengal: A preliminary assessment of ecological and human health risks - Arnob Ghosh; Kowshik Das Karmaker; Mahmudul Hasan; Mahfujur Rahman; Nusrat Jahan Shimu; Md. Saiful Islam; M. Safiur Rahman; Md. Shawon Hossain; Zulhilmi Ismail (Marine Pollution Bulletin, 2024)

Intelligent machines as information and communication technology and their influence on sustainable marketing practices for beneficial impact on business performance: A conceptual framework - Rajat Kumar Behera; Anisur Rehman; Md. Saiful Islam; Faraz Ahmad Abbasi; Asma Imtiaz (Journal of Cleaner Production, 2024)

The impact of salinity and temperature stress on survival, behaviour, immune response, and proximate composition of giant freshwater prawn Macrobrachium rosenbergii - Joyanta Bir; Haimanti Sarker; Faria Sultana Mita; Md Imran Noor; Ranajit Kumar; Shikder Saiful Islam; Mousumi Das; Khandaker Anisul Huq (Aquaculture International, 2024)

Leaching and volatilization of nitrogen in paddy rice under different nitrogen management - Majharul Islam; Md. Mizanur Rahman; Mohammad Saiful Alam; Robert Martin Rees; G. K. M. Mustafizur Rahman; Md. Giashuddin Miah; Julia Drewer; Arti Bhatia; Mark A. Sutton (Nutrient Cycling in Agroecosystems, 2024)

Soil bacteriome diversity and composition of rooftop and surface gardens in urban and peri-urban areas of Bangladesh - Md. Liton Rana; M. Nazmul Hoque; M. Shaminur Rahman; Pritom Kumar Pramanik; Md. Saiful Islam; Sadia Afrin Punom; Srinivasan Ramasamy; Pepijn Schreinemachers; Ricardo Oliva; Md. Tanvir Rahman (Environmental Monitoring and Assessment, 2024)

Appraising water resources for irrigation and spatial analysis based on fuzzy logic model in the tribal-prone areas of Bangladesh - Md. Shariful Islam; Udoy Jibon Tripura; Md. Saiful Islam; Abu Reza Md. Towfiqul Islam; S. M. Rabbi Al Zihad; Mst. Moriom Khatun; Md. Mahadi Hasan; Tuba Yasmin Lubna (Environmental Monitoring and Assessment, 2024)

Recent advances in the biosynthesis, bioavailability, toxicology, pharmacology, and controlled release of citrus neohesperidin - Saima Akhter; Md. Saiful Islam Arman; Mohammed Abu Tayab; Mohammad Nazmul Islam; Jianbo Xiao (Critical Reviews in Food Science and Nutrition, 2024)

Appraisal of metallic accumulation in the surface sediment of a fish breeding dam in Türkiye: A stochastical approach to ecotoxicological risk assessment - Bayram Yüksel; Fikret Ustaoğlu; Handan Aydın; Cem Tokatlı; Halim Topaldemir; Md Saiful Islam; Said Muhammad (Marine Pollution Bulletin, 2024)

Empowered machine learning algorithm to identify sustainable groundwater potential zone map in Jashore District, Bangladesh - Sujit Kumar Roy; Md. Mahmudul Hasan; Ismail Mondal; Javed Akhter; Sonzet Kumar Roy; Swapan Talukder; A.K.M. Saiful Islam; Atiqur Rahman; Shankar Karuppannan (Groundwater for Sustainable Development, 2024)

Assessing metal(loid)s-Induced long-term spatiotemporal health risks in Coastal Regions, Bay of Bengal: A chemometric study - Shammi Aktar; Abu Reza Md. Towfiqul Islam; Md Yousuf Mia; Jannatun Nahar Jannat; Md Saiful Islam; Md Abu Bakar Siddique; Md Abdullah Al Masud; Abubakr M. Idris; Subodh Chandra Pal; Venkatramanan Senapathi (Environmental Science and Pollution Research, 2024)

Appraisal of macro elements and trace metals in the edible fish from the Black Sea connecting coastal river, Türkiye: A preliminary study for health risk assessment - Fikret Ustaoğlu; Md. Humayun Kabir; Tapos Kormoker; Zulhilmi Ismail; Md. Saiful Islam; Beyhan Taş; Halim Topaldemir (Regional Studies in Marine Science, 2024)

Delineation of trace metal level in fish feed and farmed fish, Tilapia (Oreochromis mossumbicus) and their consequences on human health - Md. Refat Jahan Rakib; Soab Miah; M. Belal Hossain; Rakesh Kumar; Yeasmin Nahar Jolly; Shirin Akter; Md. Saiful Islam; Abubakr M. Idris (Regional Studies in Marine Science, 2024)

Linking green innovation to environmental quality in Saudi Arabia: an application of the NARDL approach - Md. Saiful Islam (Environment, Development and Sustainability, 2024)

Using unsupervised machine learning models to drive groundwater chemistry and associated health risks in Indo-Bangla Sundarban region - Jannatun Nahar Jannat; Abu Reza Md Towfiqul Islam; Md Yousuf Mia; Subodh Chandra Pal; Tanmoy Biswas; Most Mastura Munia Farjana Jion; Md Saiful Islam; Md Abu Bakar Siddique; Abubakr M. Idris; Rahat Khan; Aznarul Islam; Tapos Kormoker; et al. (Chemosphere, 2024)

Mineral production amidst the economy of uncertainty: Response of metallic and non-metallic minerals to geopolitical turmoil in Saudi Arabia - Md. Saiful Islam; Md. Monirul Islam; Anis Ur Rehman; Md. Fakhre Alam; Md. Tarique (Resources Policy, 2024)

WITHDRAWN: Trace metals translocation from soil to plants: Health risk assessment via consumption of vegetables in the urban sprawl of a developing country - KM Shamsul Haque; Md Saiful Islam; Sujat Ahmed; Md Zillur Rahman; Debolina Halder Hemy; Md Towhidul Islam; Md Kamal Hossain; Md Rafiq Uddin; Abu Reza Md Towfiqul Islam; Md Yousuf Mia; Zulhilmi Ismail; Abdullah Al Bakky; et al. (Food and Chemical Toxicology, 2024)

Corrigendum to “Finite element analysis of a light-frame wood panelized gable roof” [Eng Struct 302 (2024) 117333] - Md Saiful Islam; Ying Hei Chui (Engineering Structures, 2024)

Finite element analysis of a light-frame wood panelized gable roof - Md Saiful Islam; Ying Hei Chui (Engineering Structures, 2024)

Dynamic equity in urban amenities distribution: An accessibility-driven assessment - Fajle Rabbi Ashik; Md Saiful Islam; Md Saiful Alam; Nusrat Jahan Tabassum; Kevin Manaugh (Applied Geography, 2024)

Fractionation of environmental radioactivity in road dust from a megacity: external and internal health risks - Rahat Khan; Md. Ahosan Habib; Umma Tamim; Tapos Kormoker; Md. Harunor Rashid Khan; Md. Bazlar Rashid; Abubakr M. Idris; Saad Aldawood; Syed Mohammod Hossain; Md. Saiful Islam (Environmental Science and Pollution Research, 2024)

A review of microplastic threat mitigation in Asian lentic environments - Moriom Rahman Sadia; Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md Abdullah Al Masud; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md. Saiful Islam; Subodh Chandra Pal; Md. Refat Jahan Rakib; et al. (Journal of Contaminant Hydrology, 2024)

The path of microplastics through the rare biodiversity estuary region of the northern Bay of Bengal - Al-Nure Mubin; Abu Reza Md. Towfiqul Islam; Mehedi Hasan; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Sha Alam; Md. Refat Jahan Rakib; Muhammad Saiful Islam; Nasima Momtaz; Venkatramanan Senapathi; Abubakr M. Idris; et al. (Journal of Contaminant Hydrology, 2024)

Role of shade trees in conserving beneficial arthropods of biocontrol importance in tea ecosystem - Md. Abdul Maleque; Jannatul Ferdous; Ashika Akhter Shitel; Jaher Ahmed; A. F. M. Saiful Islam; Md. Fuad Mondal; Kamrul Hassan; Md. Abdur Razzak Choudhury; H. Roaki Ishii (Agroforestry Systems, 2024)

Bioaccumulation and sources of metal(loid)s in fish species from a subtropical river in Bangladesh: a public health concern - Mir Mohammad Ali; Khadijatul Kubra; Edris Alam; Anwar Hossain Mondol; Shahrina Akhtar; Md. Saiful Islam; Ehsanul Karim; A. S. Shafiuddin Ahmed; Md. Abu Bakar Siddique; Guilherme Malafaia; Md. Zillur Rahman; Md. Mostafizur Rahman; et al. (Environmental Science and Pollution Research, 2023)

Contamination and ecological risk assessment of Cr, As, Cd and Pb in water and sediment of the southeastern Bay of Bengal coast in a developing country - Md. Saiful Islam; Md. Towhidul Islam; Uttam Biswas Antu; Md. Sadik Mahmud Saikat; Zulhilmi Ismail; Shamsuddin Shahid; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Abdullah Al Bakky; Sujat Ahmed; Khalid A. Ibrahim; Rahmah N. Al-Qthanin; et al. (Marine Pollution Bulletin, 2023)

Analysis of self-organizing maps and explainable artificial intelligence to identify hydrochemical factors that drive drinking water quality in Haor region - Md. Yousuf Mia; Md. Emdadul Haque; Abu Reza Md Towfiqul Islam; Jannatun Nahar Jannat; Most. Mastura Munia Farjana Jion; Md. Saiful Islam; Md. Abu Bakar Siddique; Abubakr M. Idris; Venkatramanan Senapathi; Swapan Talukdar; Atiqur Rahman (Science of The Total Environment, 2023)

A GIS Framework to Demarcate Suitable Lands for Combine Harvesters Using Satellite DEM and Physical Properties of Soil - Md. Mizanur Rahman; Mohammad Kamruzzaman; Shamsuddin Shahid; Kelly R. Thorp; Hafijur Rahaman; Md. Mahir Shahriyar; A. K. M. Saiful Islam; Md. Durrul Huda (Journal of Geovisualization and Spatial Analysis, 2023)

Utilisation of probiotics for disease management in giant freshwater prawn ( Macrobrachium rosenbergii ): Administration methods, antagonistic effects and immune response - Mirja Kaizer Ahmmed; Shuva Bhowmik; Fatema Ahmmed; Stephen G. Giteru; Shikder Saiful Islam; Mayssa Hachem; Md. Ashraf Hussain; Osman N. Kanwugu; Dominic Agyei; Tom Defoirdt (Journal of Fish Diseases, 2023)
The giant freshwater prawn ( Macrobrachium rosenbergii ) is a high‐yielding prawn variety well‐received worldwide due to its ability to adapt to freshwater culture systems. Macrobrachium rosenbergii is an alternative to shrimp typically obtained from marine and brackish aquaculture systems. However, the use of intensive culture systems can lead to disease outbreaks, particularly in larval and post‐larval stages, caused by pathogenic agents such as viruses, bacteria, fungi, yeasts and protozoans. White tail disease (viral), white spot syndrome (viral) and bacterial necrosis are examples of economically significant diseases. Given the increasing antibiotic resistance of disease‐causing microorganisms, probiotics have emerged as promising alternatives for disease control. Probiotics are live active microbes that are introduced into a target host in an adequate number or dose to promote its health. In the present paper, we first discuss the diseases that occur in M. rosenbergii production, followed by an in‐depth discussion on probiotics. We elaborate on the common methods of probiotics administration and explain the beneficial health effects of probiotics as immunity enhancers. Moreover, we discuss the antagonistic effects of probiotics on pathogenic microorganisms. Altogether, this paper provides a comprehensive overview of disease control in M. rosenbergii aquaculture through the use of probiotics, which could enhance the sustainability of prawn culture.

Remittance outflow and environmental quality nexus in Saudi Arabia: the role of ICT, environmental innovation, and energy consumption - Md Saiful Islam; Anis ur Rehman; Imran Khan; Sk Habibur Rahaman (Environment, Development and Sustainability, 2023)

Receptor model-based source-specific health risks of toxic metal(loid)s in coal basin-induced agricultural soil in northwest Bangladesh - Md. Ahosan Habib; Abu Reza Md. Towfiqul Islam; Memet Varol; Khamphe Phoungthong; Rahat Khan; Md. Saiful Islam; Md. Hasanuzzaman; Md. Yousuf Mia; Romulus Costache; Subodh Chandra Pal (Environmental Geochemistry and Health, 2023)

Fuzzy logic, geostatistics, and multiple linear models to evaluate irrigation metrics and their influencing factors in a drought-prone agricultural region - S.M. Rabbi Al Zihad; Abu Reza Md Towfiqul Islam; Md Abu Bakar Siddique; Md Yousuf Mia; Md Saiful Islam; Md Aminul Islam; A.B.M. Mainul Bari; Md Bodrud-Doza; Sobhy M. Yakout; Venkatramanan Senapathi; Sumanta Chatterjee (Environmental Research, 2023)

Coastal aquaculture in Bangladesh: Sundarbans's role against climate change - Shahanaj Parvin; Md. Hashmi Sakib; Md. Latiful Islam; Christopher L. Brown; Md. Saiful Islam; Yahia Mahmud (Marine Pollution Bulletin, 2023)

RETRACTED: Managing the invisible threat of microplastics in marine ecosystems: Lessons from coast of the Bay of Bengal - Al-Nure Mubin; Shahoriar Arefin; Md. Sonir Mia; Abu Reza Md. Towfiqul Islam; A.B.M. Mainul Bari; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; M. Safiur Rahman; Venkatramanan Senapathi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2023)

Correction to: Human exposures to multiple water sources in the southwestern coastal region of Bangladesh: water quality, pollution sources, and preliminary health risks appraisals - Md Bazlar Rashid; Md Abu Bakar Siddique; Rahat Khan; Md Ahosan Habib; Md Saiful Islam; Md Ahedul Akbor; A. J. M. Emdadul Haque; Md Rubel Sheik; Mohammad Alamgir Kabir; Md Nuruddin Sarker; Abubakr M. Idris (Environmental Science and Pollution Research, 2023)

The pervasiveness of microplastic contamination in the gastrointestinal tract of fish from the western coast of Bangladesh - Marhaba Matluba; Md. Kawser Ahmed; K.M. Azam Chowdhury; Nasim Khan; Md. Asrafur Rahman Ashiq; Muhammad Saiful Islam (Marine Pollution Bulletin, 2023)

RETRACTED: Personal protective equipment-derived pollution during Covid-19 era: A critical review of ecotoxicology impacts, intervention strategies, and future challenges - Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md. Saiful Islam; Subodh Chandra Pal; Aznarul Islam; Tasrina Rabia Choudhury; Md. Refat Jahan Rakib; et al. (Science of The Total Environment, 2023)

BARI Alu-86—An Early-Bulker, High Yielding and Quality Potato (Solanum tuberosum L.) Cultivar Suitable for Diverse Environments - Sauda Naznin; Md. Mazadul Islam; Md Abu Kawochar; Bimal Chandra kundu; Zulfikar Haider Prodhan; Md Nurul Amin; Md. Nasir Uddin; Md Salim; Babul Anwar; Protima Rani Sarker; Saiful Islam; Afroz Naznin; et al. (American Journal of Potato Research, 2023)

Human exposures to multiple water sources in the southwestern coastal region of Bangladesh: water quality, pollution sources, and preliminary health risks appraisals - Md Bazlar Rashid; Md Abu Bakar Siddique; Rahat Khan; Md Ahosan Habib; Md Saiful Islam; Md Ahedul Akbor; A. J. M. Emdadul Haque; Md Rubel Sheik; Mohammad Alamgir Kabir; Md Nuruddin Sarker; Abubakr M. Idris (Environmental Science and Pollution Research, 2023)

Microplastic as an invisible threat to the coral reefs: Sources, toxicity mechanisms, policy intervention, and the way forward - Md. Naimur Rahman; Sajjad Hossain Shozib; Mst. Yeasmin Akter; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Salman Sohel; Chinnaperumal Kamaraj; Md. Refat Jahan Rakib; Abubakr M. Idris; Aniruddha Sarker; Guilherme Malafaia (Journal of Hazardous Materials, 2023)

Correction to: The asymmetric effect of ICT on CO2 emissions in the context of an EKC framework in GCC countries: the role of energy consumption, energy intensity, trade, and financial development - Md. Saiful Islam; Sk Habibur Rahaman (Environmental Science and Pollution Research, 2023)

Pollution trends and ecological risks of heavy metal(loid)s in coastal zones of Bangladesh: A chemometric review - Jannatun Nahar Jannat; Md. Yousuf Mia; Most. Mastura Munia Farjana Jion; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Refat Jahan Rakib; Sobhy M. Ibrahim; Subodh Chandra Pal; Romulus Costache; Guilherme Malafaia; Abu Reza Md Towfiqul Islam (Marine Pollution Bulletin, 2023)

Abundance, characteristics, and ecological risks of microplastics in the riverbed sediments around Dhaka city - Md. Saiful Islam; Md. Rezaul Karim; Md Tanvirul Islam; Humaira Tasnim Oishi; Zarin Tasnim; Harinarayan Das; A. H. M. Enamul Kabir; Masahiko Sekine (Science of The Total Environment, 2023)

A critical review and prospect of NO2 and SO2 pollution over Asia: Hotspots, trends, and sources - Most. Mastura Munia Farjana Jion; Jannatun Nahar Jannat; Md. Yousuf Mia; Md. Arfan Ali; Md. Saiful Islam; Sobhy M. Ibrahim; Subodh Chandra Pal; Aznarul Islam; Aniruddha Sarker; Guilherme Malafaia; Muhammad Bilal; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Microplastics in aquatic environments: A comprehensive review of toxicity, removal, and remediation strategies - A.S. Shafiuddin Ahmed; Md Masum Billah; Mir Mohammad Ali; Md Khurshid Alam Bhuiyan; Laodong Guo; Mohammad Mohinuzzaman; M. Belal Hossain; M. Safiur Rahman; Md Saiful Islam; Meng Yan; Wenlong Cai (Science of The Total Environment, 2023)

Heterogeneous impacts of home-gardening on household food and nutrition security in Rwanda - Gazali Issahaku; Lukas Kornher; Abu Hayat Md. Saiful Islam; Awal Abdul-Rahaman (Food Security, 2023)
This study examines farmers’ decisions to engage in subsistence home-gardening and its impact on food and nutrition security among farm households in Rwanda under diverse conditions. The study uses a nationally representative dataset from Rwanda from 2012, 2015, and 2018. We employ an endogenous switching regression model to jointly estimate the drivers of home-gardening participation decisions and food and nutrition security outcomes, whiles accounting for selection bias from observable and unobservable factors. We also estimate the treatment effects of home-gardening participation on dietary diversity, food consumption score, and anthropometric markers of women and children. The treatment effects are calculated at sample means and connected to market-related variables, such as land ownership, commercialization extent, and market distance. We find that having a home-garden is linked to improved dietary diversity and better nutritional outcomes. If households have restricted access to land and reside further away from marketplaces, the benefits are larger. In contrast, the benefits of home-gardening are positive and significant regardless of the level of commercialization of production. We also discover that family size, gender, education, access to land, and livestock ownership are statistically significant drivers of home-gardening participation in Rwanda. However, the amount of commercialization did not affect a household’s decision to participate in home-gardening.

The asymmetric effect of ICT on CO2 emissions in the context of an EKC framework in GCC countries: the role of energy consumption, energy intensity, trade, and financial development - Md. Saiful Islam; Sk Habibur Rahaman (Environmental Science and Pollution Research, 2023)

Future scenarios of fish supply and demand for food and nutrition security in Bangladesh: An analysis with the AsiaFish model - Nhuong Tran; U-Primo Rodriguez; Chin Yee Chan; Yee Mon Aung; Long Chu; Abu Hayat Md. Saiful Islam; Benoy Kumar Barman; Michael John Phillips (Aquaculture, 2023)

Effects of straw incorporation and straw-burning on aggregate stability and soil organic carbon in a clay soil of Bangladesh - Milton Halder; Shahnewaz Jim Ahmad; Tanvir Rahman; Jagadish Chandra Joardar; Md. Abu Bakar Siddique; Muhammad Saiful Islam; Mahbub Ul Islam; Shuai Liu; Sheikh Rabbi; Xinhua Peng (Geoderma Regional, 2023)

An efficient flash flood forecasting system for the un-gaged Meghna basin using open source platform Delft-FEWS - Md. Enayet Chowdhury; AKM Saiful Islam; Matthijs Lemans; Mark Hegnauer; Ashfaqur Rahaman Sajib; Nahruma Mehzabeen Pieu; Mohan Kumar Das; Nur Shadia; Akramul Haque; Binata Roy; Maruf Billah; Faruque Abdullah; et al. (Environmental Modelling & Software, 2023)

Assessment of flood vulnerability in Jamuna floodplain: a case study in Jamalpur district, Bangladesh - Md. Munjurul Haque; Sabina Islam; Md. Bahuddin Sikder; Md. Saiful Islam; Annyca Tabassum (Natural Hazards, 2023)

Grain size analysis and ecological risk assessment of metals in the sediments of Konsin River and Igboho dam reservoir, Oyo State, Nigeria, under agricultural disturbances - Henry Chima Asomba; Bede Izuchukwu Ezewudo; Chioma Janefrances Okeke; Md. Saiful Islam (Environmental Monitoring and Assessment, 2023)

Comparative genomics with evolutionary lineage in Streptomyces bacteria reveals high biosynthetic potentials - Khorshed Alam; Md. Mahmudul Islam; Saiful Islam; Jinfang Hao; Muhammad Nazeer Abbasi; Muhammad Hayat; Muhammad Shoaib; Youming Zhang; Aiying Li (World Journal of Microbiology and Biotechnology, 2023)

Poromechanics of Fractured/Faulted Reservoirs During Fluid Injection Based on Continuum Damage Modeling and Machine Learning - Fethi Abbassi; Ali Karrech; Md Saiful Islam; Abdennour C. Seibi (Natural Resources Research, 2023)

TGFβ1 rs1800469 and SMAD4 rs10502913 polymorphisms and genetic susceptibility to colorectal cancer in Bangladeshi population - Taposhi Nahid Sultana; Nusrat Islam Chaity; Md. Mehedi Hasan; Ishrat Islam Shrabonee; Sanzana Fareen Rivu; Md. Abdul Aziz; Shaid All Sahaba; Mohd Nazmul Hasan Apu; Noor Ahmed Nahid; Mohammad Safiqul Islam; Md. Saiful Islam (Molecular Biology Reports, 2023)

Assessment of microplastics pollution in aquatic species (fish, crab, and snail), water, and sediment from the Buriganga River, Bangladesh: An ecological risk appraisals - Md. Rashedul Haque; Mir Mohammad Ali; Wahida Ahmed; Md. Abu Bakar Siddique; Md. Ahedul Akbor; Md. Saiful Islam; Md. Mostafizur Rahman (Science of The Total Environment, 2023)

Effects of COVID-19 era on a subtropical river basin in Bangladesh: Heavy metal(loid)s distribution, sources and probable human health risks - Jawad-Ul-Haque; Md. Abu Bakar Siddique; Md. Saiful Islam; Mir Mohammad Ali; Cem Tokatli; Aznarul Islam; Subodh Chandra Pal; Abubakar M. Idris; Guilherme Malafaia; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Hydrochemical appraisal of surface water from a subtropical urban river in southwestern Bangladesh using indices, GIS, and multivariate statistical analysis - Rifat Shahid Shammi; Md. Saddam Hossain; Md. Humayun Kabir; Md. Saiful Islam; Md. Tajul Islam Taj; Md. Shafiqul Islam; Md. Eusuf Sarker; Md. Samrat Hossain; Abubakr M. Idris (Environmental Science and Pollution Research, 2023)

Correction to: Arsenic in the foodstuffs: potential health appraisals in a developing country, Bangladesh - Md. Saiful Islam; Ramal Ahmed Mustafa; Khamphe Phoungthong; Abu Reza Md Towfiqul Islam; Tofazzal Islam; Tasrina Rabia Choudhury; Md. Humayun Kabir; Mir Mohammad Ali; Abubakr M. Idris (Environmental Science and Pollution Research, 2022)

Arsenic in the foodstuffs: potential health appraisals in a developing country, Bangladesh - Md. Saiful Islam; Ramal Ahmed Mustafa; Khamphe Phoungthong; Abu Reza Md Towfiqul Islam; Tofazzal Islam; Tasrina Rabia Choudhury; Md. Humayun Kabir; Mir Mohammad Ali; Abubakr M. Idris (Environmental Science and Pollution Research, 2022)

Distribution, sources, and pollution levels of toxic metal(loid)s in an urban river (Ichamati), Bangladesh using SOM and PMF modeling with GIS tool - Md Nasiruddin; Abu Reza Md Towfiqul Islam; Md Abu Bakar Siddique; Md Hasanuzaman; Md Mahedi Hassan; Md Ahedul Akbor; Mehedi Hasan; Md Saiful Islam; Rahat Khan; Md Al Amin; Subodh Chandra Pal; Abubakr Mustafa Idris; et al. (Environmental Science and Pollution Research, 2022)

Abundance, characteristics, and spatial–temporal distribution of microplastics in sea salts along the Cox’s Bazar coastal area, Bangladesh - Muhammad Saiful Islam; Md. Rashed Hasan; Zahidul Islam (Environmental Science and Pollution Research, 2022)

Influence of COVID-19 on the sustainability of livestock performance and welfare on a global scale - Md. Tanvir Rahman; Md. Saiful Islam; Awad A. Shehata; Shereen Basiouni; Hafez M. Hafez; Esam I. Azhar; Asmaa F. Khafaga; Fulvia Bovera; Youssef A. Attia (Tropical Animal Health and Production, 2022)

Modeling with strategies to control the adverse effects of global warming on marine ecosystems - Sajib Mandal; Md. Sirajul Islam; Md. Haider Ali Biswas; Saiful Islam (Modeling Earth Systems and Environment, 2022)

A comprehensive review of heavy metal pollution in the coastal areas of Bangladesh: abundance, bioaccumulation, health implications, and challenges - Md.Refat Jahan Rakib; Md. Asrafur Rahman; Amarachi Paschaline Onyena; Rakesh Kumar; Aniruddha Sarker; M. Belal Hossain; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Mostafizur Rahman; Yeasmin Nahar Jolly; Abubakr M. Idris; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2022)

Groundwater level estimation in northern region of Bangladesh using hybrid locally weighted linear regression and Gaussian process regression modeling - Ahmed Elbeltagi; Roquia Salam; Subodh Chandra Pal; Bilel Zerouali; Shamsuddin Shahid; Javed Mallick; Md. Saiful Islam; Abu Reza Md. Towfiqul Islam (Theoretical and Applied Climatology, 2022)

Spatiotemporal variation and toxicity of trace metals in commercially important fish of the tidal Pasur River in Bangladesh - Mir Mohammad Ali; Mohammad Lokman Ali; Md. Simul Bhuyan; Md. Saiful Islam; Md. Zillur Rahman; Md. Wahidul Alam; Monika Das; Sobnom Mustary; Md. Nazrul Islam (Environmental Science and Pollution Research, 2022)

Potentially toxic elemental contamination in Wainivesi River, Fiji impacted by gold-mining activities using chemometric tools and SOM analysis - Satendra Kumar; Abu Reza Md Towfiqul Islam; Md. Hasanuzzaman; Roquia Salam; Md. Saiful Islam; Rahat Khan; M Safiur Rahman; Subodh Chandra Pal; Mir Mohammad Ali; Abubakr M Idris; Williamson Gustave; Ahmed Elbeltagi (Environmental Science and Pollution Research, 2022)

Do personal remittances cause environmental pollution? Evidence from the top eight remittance-receiving countries - Md. Saiful Islam (Environmental Science and Pollution Research, 2022)

Ecological and probabilistic human health hazard assessment of heavy metals in Sera Lake Nature Park sediments (Trabzon, Turkey) - Fikret Ustaoğlu; Md Saiful Islam; Cem Tokatli (Arabian Journal of Geosciences, 2022)

The link of ERCC2 rs13181 and ERCC4 rs2276466 polymorphisms with breast cancer in the Bangladeshi population - Shaid All Sahaba; Mohammad Abdur Rashid; Md. Saiful Islam; Noor Ahmed Nahid; Mohd Nazmul Hasan Apu; Taposhi Nahid Sultana; Nusrat Islam Chaity; Md. Mehedi Hasan; Mohammad Safiqul Islam (Molecular Biology Reports, 2022)

Molecular characterization of Cucumber mosaic virus subgroup II isolate associated with cucumber in Bangladesh - Tridib Kumar Paul; Mohammad Mahmood Hasan; Tasnin Khan Eusufzai; Md. Moniruzzaman Hasan; Saiful Islam; Fareyzul Haque Ansarey; Mohammad Nurul Islam; Abu Shamim Mohammad Nahiyan (Indian Phytopathology, 2022)

Road dust–driven elemental distribution in megacity Dhaka, Bangladesh: environmental, ecological, and human health risks assessment - Tapos Kormoker; Md. Humayun Kabir; Rahat Khan; Md. Saiful Islam; Rifat Shahid Shammi; Mamun Abdullah Al; Ram Proshad; Umma Tamim; Md. Eusuf Sarker; Md. Tajul Islam Taj; Ayesha Akter; Abubakr M. Idris (Environmental Science and Pollution Research, 2022)

Ecotoxicological risk assessment for sediments of Çavuşlu stream in Giresun, Turkey: association between garbage disposal facility and metallic accumulation - Bayram Yüksel; Fikret Ustaoğlu; Cem Tokatli; Md Saiful Islam (Environmental Science and Pollution Research, 2022)

Higher seasonal temperature enhances the occurrence of methicillin resistance of Staphylococcus aureus in house flies (Musca domestica) under hospital and environmental settings - Md. Abdus Sobur; Md. Saiful Islam; Zobayda Farzana Haque; Ebiowei Samuel F. Orubu; Antonio Toniolo; Md. Abu Choudhury; Md. Tanvir Rahman (Folia Microbiologica, 2022)

Does financial development cause environmental pollution? Empirical evidence from South Asia - Md. Saiful Islam (Environmental Science and Pollution Research, 2022)

Spatiotemporal variations and bio-geo-ecological risk assessment of heavy metals in sediments of a wetland of international importance in Turkey - Cem Tokatli; Md Saiful Islam (Arabian Journal of Geosciences, 2022)

QbD Approach towards Robust Design Space for Flutamide/PiperineSelf-Emulsifying Drug Delivery System with Reduced Liver Injury - Mithun Saha; Pallabi Sikder; Aditi Saha; Sharha Shah; Sharmin Sultana; Tushar Emran; Ananna Banik; Zahidul Islam; Muhammad Saiful Islam; Shazid Md. Sharker; Hasan Mahmud Reza (AAPS PharmSciTech, 2022)

Hydrological distribution of physicochemical parameters and heavy metals in surface water and their ecotoxicological implications in the Bay of Bengal coast of Bangladesh - Md. Saiful Islam; Abubakr M. Idris; Abu Reza Md. Towfiqul Islam; Mir Mohammad Ali; Md. Refat Jahan Rakib (Environmental Science and Pollution Research, 2021)

Potentially toxic elements in street dust from an urban city of a developing country: ecological and probabilistic health risks assessment - Md. Humayun Kabir; Tapos Kormoker; Md. Saiful Islam; Rahat Khan; Rifat Shahid Shammi; Tanmoy Roy Tusher; Ram Proshad; Md Shafiqul Islam; Abubakr M. Idris (Environmental Science and Pollution Research, 2021)

Comprehensive evaluation of chemical properties and toxic metals in the surface water of Louhajang River, Bangladesh - Ram Proshad; Dan Zhang; Abubakr Mustafa Idris; Md. Saiful Islam; Tapos Kormoker; Md Nazirul Islam Sarker; Sujan Khadka; Abu Sayeed; Maksudul Islam (Environmental Science and Pollution Research, 2021)

Alkali and Intensified Heat Treatment of Corn Stalk for Bioethanol Production - Taposhi Rabeya; Farjana Jehadin; Mohammad A. Asad; Olubunmi O. Ayodele; Abiodun E. Adekunle; Md. Saiful Islam (Sugar Tech, 2021)

A Comparative Study of Geometrical Upscaling Methods for Inclusion of Fault Zone Structure into Upscaled Reservoir Simulation Models - Md. Saiful Islam; Tom Manzocchi; John J. Walsh; David Stern (Natural Resources Research, 2021)

Investigation of trace metals in riverine waterways of Bangladesh using multivariate analyses: spatial toxicity variation and potential health risk assessment - Ram Proshad; Mamun Abdullah Al; Md. Saiful Islam; Sujan Khadka; Tapos Kormoker; Minhaz Uddin; Letizia Modeo (Environmental Science and Pollution Research, 2021)

Preliminary assessment of trace elements in surface and deep waters of an urban river (Korotoa) in Bangladesh and associated health risk - Md Saiful Islam (Environmental Science and Pollution Research, 2021)

Effect of COVID-19 pandemic-induced lockdown (general holiday) on air quality of Dhaka City - Md. Saiful Islam; Tahmid Anam Chowdhury (Environmental Monitoring and Assessment, 2021)

Growth kinetics of a Vero cells adapted Bangladeshi strain of peste des petits ruminants (PPR) virus in cell culture - Md. Saiful Islam Siddiqui; Md. Rafiqul Islam; Emdadul Haque Chowdhury (Archives of Microbiology, 2021)

Development of potential map for groundwater abstraction in the northwest region of Bangladesh using RS-GIS-based weighted overlay analysis and water-table-fluctuation technique - Sara Nowreen; Imran Hossain Newton; Rashed Uz Zzaman; A. K. M. Saiful Islam; G. M. Tarekul Islam; Md. Saiful Alam (Environmental Monitoring and Assessment, 2021)

Preliminary Assessment of Uranium Contamination in Drinking Water Sources Near a Uranium Mine in the Siavonga District, Zambia, and Associated Health Risks - Titus Haakonde; John Yabe; Kennedy Choongo; Gershom Chongwe; Md. Saiful Islam (Mine Water and the Environment, 2020)

Appraisal of heavy metal contamination in sediments of the Shitalakhya River in Bangladesh using pollution indices, geo-spatial, and multivariate statistical analysis - Md. Humayun Kabir; Md. Sirajul Islam; Md. Enamul Hoq; Tanmoy Roy Tusher; Md. Saiful Islam (Arabian Journal of Geosciences, 2020)

Synoptic flow patterns and large-scale characteristics of flash flood-producing rainstorms over northeast Bangladesh - Mohan K. Das; A. K. M. Saiful Islam; Samarendra Karmakar; Md. Jamal Uddin Khan; Khaled Mohammed; G. M. Tarekul Islam; Sujit Kumar Bala; Thomas M. Hopson (Meteorology and Atmospheric Physics, 2020)

Viral contamination of tiger shrimp Penaeus monodon broodstock in Bangladesh - Dipankar Chakrobortty; Md. Rayhan Ali; Bipul Kumar Dey; Nipa Gupta; Shikder Saiful Islam; Liying Sui (Aquaculture International, 2020)

SMAD2 rs4940086 heterozygosity increases the risk of cervical cancer development among the women in Bangladesh - Parsa Sanjana Haque; Mohd Nazmul Hasan Apu; Noor Ahmed Nahid; Farhana Islam; Md Reazul Islam; Abul Hasnat; Md Saiful Islam (Molecular Biology Reports, 2020)

Changes in climate extremes over Bangladesh at 1.5 °C, 2 °C, and 4 °C of global warming with high-resolution regional climate modeling - Md Jamal Uddin Khan; A. K. M. Saiful Islam; Sujit Kumar Bala; G. M. Tarekul Islam (Theoretical and Applied Climatology, 2020)

An intra-household analysis of farmers’ perceptions of and adaptation to climate change impacts: empirical evidence from drought prone zones of Bangladesh - A. K. M. Abdullah Al-Amin; Tahmina Akhter; Abu Hayat Md. Saiful Islam; Hasneen Jahan; M. J. Hossain; Md. Masudul Haque Prodhan; Mohammed Mainuddin; Mac Kirby (Climatic Change, 2019)

Autophagy-mediated Nutrient Recycling and Regulation in Plants: A Molecular View - Md. Saiful Islam; Ram Proshad; Tapos Kormoker; Tanmoy Roy Tusher (Journal of Plant Biology, 2019)

Drought adaptation measures and their effectiveness at Barind Tract in northwest Bangladesh: a perception study - Md. Saiful Islam; Md. Zakir Hossain; Md. Bahuddin Sikder (Natural Hazards, 2019)

Distribution of polycyclic aromatic hydrocarbons (PAHs) in commonly consumed seafood from coastal areas of Bangladesh and associated human health implications - Md. Habibullah-Al-Mamun; Md. Kawser Ahmed; Md. Saiful Islam; Masahiro Tokumura; Shigeki Masunaga (Environmental Geochemistry and Health, 2019)

Green manuring effects on crop morpho-physiological characters, rice yield and soil properties - Md. Moshiul Islam; Tahmina Akter Urmi; Md. Sohel Rana; Mohammad Saiful Alam; M. Moynul Haque (Physiology and Molecular Biology of Plants, 2019)

Polychlorinated biphenyls (PCBs) in commonly consumed seafood from the coastal area of Bangladesh: occurrence, distribution, and human health implications - Md. Habibullah-Al-Mamun; Md. Kawser Ahmed; Md. Saiful Islam; Anwar Hossain; Masahiro Tokumura; Shigeki Masunaga (Environmental Science and Pollution Research, 2019)

Topography of the intertidal zone along the shoreline of Chittagong (Bangladesh) using PROBA-V imagery - Matthias Bergmann; Fabien Durand; Yann Krien; Md. Jamal Uddin Khan; Marufa Ishaque; Laurent Testut; Stéphane Calmant; Philippe Maisongrande; A.K.M. Saiful Islam; Fabrice Papa; Sylvain Ouillon (International Journal of Remote Sensing, 2018)

Evaluation of Microphysics and Cumulus Schemes of WRF for Forecasting of Heavy Monsoon Rainfall over the Southeastern Hilly Region of Bangladesh - Md Alfi Hasan; A. K. M. Saiful Islam (Pure and Applied Geophysics, 2018)

Assessing climatic trends of extreme rainfall indices over northeast Bangladesh - Md. Abul Basher; Mathew Alexander Stiller-Reeve; A. K. M. Saiful Islam; Scott Bremer (Theoretical and Applied Climatology, 2018)

Farm diversification and food and nutrition security in Bangladesh: empirical evidence from nationally representative household panel data - Abu Hayat Md. Saiful Islam; Joachim von Braun; Andrew L. Thorne-Lyman; Akhter U. Ahmed (Food Security, 2018)

Regional changes of precipitation and temperature over Bangladesh using bias‐corrected multi‐model ensemble projections considering high‐emission pathways - Md. Golam Rabbani Fahad; A. K. M. Saiful Islam; Rouzbeh Nazari; M. Alfi Hasan; G. M. Tarekul Islam; Sujit Kumar Bala (International Journal of Climatology, 2018)
A multi‐model ensemble provides useful information about the uncertainty of the future changes of climate. High‐emission scenarios using representative concentration pathways (RCP8.5) of the Fifth Phase Coupled Model Inter‐comparison Project (CMIP5) in the Intergovernmental Panel on Climate Change (IPCC) also aids to capture the possible extremity of the climate change. Using the CMIP5 regional climate modelling predictions, this study analyses the distribution of the temperature and precipitation in Bangladesh in the recent years (1971–2000) and in three future periods (2010–2040, 2041–2070 and 2070–2100) considering RCP8.5 scenarios. Climate changes are expressed in terms of 30‐year return values of annual near‐surface temperature and 24‐h precipitation amounts. At the end of the century, the mean temperature increase over Bangladesh among the 11 RCMs will vary from 5.77 to 3.24 °C. Spatial analysis of the 11 RCMs exhibited that the southwest and the south central parts of Bangladesh will experience a greater temperature rise in the future. Possible changes in rainfall are also exhibited both temporally and spatially. Based on the analysis of all the RCMs, a significant increase of rainfall in the pre‐ and post‐monsoon period is observed. It is also evident that monsoon rainfall will not increase in comparison with pre‐monsoon season. Zonal statistics of 64 districts of Bangladesh are also conducted for the 2020s, 2050s and 2080s to find out the most exposed regions in terms of the highest rise in temperature and changes in precipitation.

Extreme flows and water availability of the Brahmaputra River under 1.5 and 2 °C global warming scenarios - Khaled Mohammed; Akm Saiful Islam; GM Tarekul Islam; Lorenzo Alfieri; Sujit Kumar Bala; Md. Jamal Uddin Khan (Climatic Change, 2017)

Arsenic in the food chain and assessment of population health risks in Bangladesh - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Dennis Wayne Eaton (Environment Systems and Decisions, 2017)

Trace metal contamination in commercial fish and crustaceans collected from coastal area of Bangladesh and health risk assessment - Mohammad Raknuzzaman; Md Kawser Ahmed; Md Saiful Islam; Md Habibullah-Al-Mamun; Masahiro Tokumura; Makoto Sekine; Shigeki Masunaga (Environmental Science and Pollution Research, 2016)

Health risk assessment due to heavy metal exposure from commonly consumed fish and vegetables - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Mohammad Raknuzzaman; Mir Mohammad Ali; Dennis Wayne Eaton (Environment Systems and Decisions, 2016)

Health risk assessment of trace elements via dietary intake of ‘non-piscine protein source’ foodstuffs (meat, milk and egg) in Bangladesh - Nazma Shaheen; Md. Kawser Ahmed; Md. Saiful Islam; Md. Habibullah-Al-Mamun; Avonti Basak Tukun; Saiful Islam; Abu Torab M.A. Rahim (Environmental Science and Pollution Research, 2016)

Apportionment of heavy metals in soil and vegetables and associated health risks assessment - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun (Stochastic Environmental Research and Risk Assessment, 2016)

Human health risk assessment of heavy metals in tropical fish and shellfish collected from the river Buriganga, Bangladesh - Md. Kawser Ahmed; Mohammad Abdul Baki; Md. Saiful Islam; Goutam Kumar Kundu; Md. Habibullah-Al-Mamun; Santosh Kumar Sarkar; Md. Muzammel Hossain (Environmental Science and Pollution Research, 2015)

Trace elements in different land use soils of Bangladesh and potential ecological risk - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Mohammad Raknuzzaman (Environmental Monitoring and Assessment, 2015)

Trace elements in two staple cereals (rice and wheat) and associated health risk implications in Bangladesh - Md. Kawser Ahmed; Nazma Shaheen; Md. Saiful Islam; Md. Habibullah-Al-Mamun; Saiful Islam; Cadi Parvin Banu (Environmental Monitoring and Assessment, 2015)

Metal speciation in soil and health risk due to vegetables consumption in Bangladesh - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun (Environmental Monitoring and Assessment, 2015)

Metal Speciation in Sediment and Their Bioaccumulation in Fish Species of Three Urban Rivers in Bangladesh - Md Saiful Islam; Md Kawser Ahmed; Mohammad Raknuzzaman; Md Habibullah-Al-Mamun; Shigeki Masunaga (Archives of Environmental Contamination and Toxicology, 2015)

Arsenic and lead in foods: a potential threat to human health in Bangladesh - Md Saiful Islam; Md Kawser Ahmed; Md Habibullah-Al-Mamun; Kazi Nazrul Islam; Md Ibrahim; Shigeki Masunaga (Food Additives & Contaminants: Part A, 2014)

Trace metals in soil and vegetables and associated health risk assessment - Md Saiful Islam; Md Kawser Ahmed; Md Habibullah-Al-Mamun; Shigeki Masunaga (Environmental Monitoring and Assessment, 2014)

Direct and admixture toxicity of diatomaceous earth and monoterpenoids against the storage pests Callosobruchus maculatus (F.) and Sitophilus oryzae (L.) - Md. Saiful Islam; Md. Mahbub Hasan; Chaoliang Lei; Tanja Mucha-Pelzer; Inga Mewis; Christian Ulrichs (Journal of Pest Science, 2010)

Comparative Analysis of Serum Manganese, Zinc, Calcium, Copper and Magnesium Level in Panic Disorder Patients - Zabun Nahar; Mohammad Abul Kalam Azad; Md Ashrafur Rahman; Mohammad Arifur Rahman; Wasimul Bari; Sheikh Nazrul Islam; Md Saiful Islam; Abul Hasnat (Biological Trace Element Research, 2010)